PENGGUNAAN MEDIA PEMBELAJARAN VIDEOSCRIBE UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Rahma Dilla Zainuri; Mitra Sasmita; Haerudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning media is a very important part of the learning process because it is a tool and method used by teachers to convey information in the classroom. There are many innovations happening in the world of education today, one of which is the use of Videoscribe, an animation design application with a white background like a blackboard. Based on the results of observations and interviews with grade V students of Madrasah Ibtidaiyyah Al-Ianah, it was found that students' learning motivation was still low because the use of media was less interesting. The purpose of this research is to create Videoscribe-based learning media. The research instruments are observation and interview, while the analysis method is based on linguistic data such as notes, comments, suggestions and criticisms from students and peers. The results of this study can make learning more interesting, increase student motivation, avoid boredom, and train student thinking from concrete to abstract and simple to complex Students can place visual elements together. Connect the overall visual message with your own experience. Draw conclusions from what you visualise. Then, create new concepts based on what you learnt earlier.